2021
DOI: 10.3389/fphar.2021.713200
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin A, a Triterpene Saponin, Suppresses Angiogenesis and Tumor Growth by Blocking VEGFR2-Mediated Signaling Pathway

Abstract: Saikosaponin A (SSA), a main triterpenoid saponin component from Radix Bupleurum, has been revealed to have a variety of pharmacological activities. However, whether SSA can inhibit angiogenesis, a key step in solid tumor progression, remains unknown. In this study, we demonstrated that SSA could powerfully suppress the proliferation, migration, and tube formation of human umbilical vein endothelial cells. SSA also significantly inhibited angiogenesis in the models of the chick embryo chorioallantoic membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A series of antiangiogenic drugs have been invented and approved for clinical applications against different cancers, such as antibodies (bevacizumab, ranibizumab, and ramucirumab), small kinase inhibitors (lenvatinib, pazopanib, and sorafenib), and fusion proteins (aflibercept) [25][26][27][28]. However, clinical observations have shown that these reagents may cause a broad spectrum of toxic side effects and unsatisfied pharmacokinetic behavior, and eventually develop resistance and limit therapeutic outcomes [29,30]. Therefore, novel medicines with higher efficacy and minor toxic side effects against tumor angiogenesis are urgently warranted.…”
Section: Introductionmentioning
confidence: 99%
“…A series of antiangiogenic drugs have been invented and approved for clinical applications against different cancers, such as antibodies (bevacizumab, ranibizumab, and ramucirumab), small kinase inhibitors (lenvatinib, pazopanib, and sorafenib), and fusion proteins (aflibercept) [25][26][27][28]. However, clinical observations have shown that these reagents may cause a broad spectrum of toxic side effects and unsatisfied pharmacokinetic behavior, and eventually develop resistance and limit therapeutic outcomes [29,30]. Therefore, novel medicines with higher efficacy and minor toxic side effects against tumor angiogenesis are urgently warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of ginsenoside Rk3, raddeanin A, saikosaponin A and oldhamianoside II in chick embryo CAM assay confirmed their antiangiogenic activity (Wang et al 2013a;Duan et al 2017;Wu et al 2021a;Zhang et al 2021). The latter also decreased microvessel density in the tumor in the xenograft model, while saikosaponin A additionally inhibited angiogenesis in a dose-dependent manner in the Matrigel plug assay (Zhang et al 2021).…”
Section: Triterpene Saponins Active In In Vivo Models Of Pancreatic C...mentioning
confidence: 70%
“…One of the well-known triterpene saponins that was shown to be one of the relatively potent agents is a-hederin which dose-dependently reduced gastric tumors in mice (Wang et al 2020a). Another widely studied compound, saikosaponin A, reduced the development of HCT15-colorectal-cancer-cells-induced tumors in mice (Zhang et al 2021). The suggested mechanism was linked to inhibition of angiogenesis.…”
Section: Triterpene Saponins Active In In Vivo Models Of Breast Cancermentioning
confidence: 99%